Monetary policy transmission to small business loan performance: Evidence from loan-level data - Rodrigo Sekkel; Tamon Takamura; Yaz Terajima (Bank of Canada, 2024)
This paper analyzes the dynamic and heterogeneous responses of loan performance to a monetary-policy shock using loan-level panel data for small-scale private firms in Canada. Our dataset contains detailed loan characteristics information that allows us to distinguish the effects of the aggregate-demand channel, which affects loan performance through general-equilibrium effects, and the cash-flow channel that directly impacts debt service of firms through variable rates. We find that the effects on loan performance through both channels materialize with a delay and are persistent over time. The peak effect of the cash-flow channel is as large as that of the aggregate-demand channel. Moreover, we investigate whether collateral can reduce the sensitivity of variable-rate loan performance to a policy-rate shock through an ex post disciplinary effect that incentivizes loan repayment by small firms. We find that collateral induces repayment incentives of borrowers relative to unsecured loans but only for ex ante safe loans that are used for investment rather than for other purposes such as working capital. This implies that collateral has a limited impact on reducing financial frictions of small firms.
Keywords: C32; E17; E37; E52; 330; Monetary policy transmission; Firm dynamics